URUTAN PARSIAL PADA SEMIGRUP DAN PADA KELAS-KELAS DARI SUATU SEMIGRUP - Irtrianta Pasangka Irtrianta Pasangka (Jurnal Matematika, 2016)
ABSTRACK. Non empty set  with binary operation  is called semigroup if the binary operation on  is associative. An element a of semigroup  is called regular if there exist  such that  and semigroup  is called invers if there exist  such that  dan . Partial order is relation which is satisfy reflexive, antysymetric and transitive. Relation  dan  is equivalent relation. Let  be semigroup and  relation for every ,  is  class that contain . Thus obtain on relations  dan . Relation  is called partially order relation of regular semigroup  if for any ,  if and only if  and  for some . Relation  is called partially order relation of regular semigroup  if for any ,  if and only if  for some .